Molecular and physiological characterization of the effects of auxin-enriched rootstock on grafting. (1st April 2021) - Zhai, Longmei; Wang, Xiaomin; Tang, Dan; Qi, Qi; Yer, Huseyin; Jiang, Xiangning; Han, Zhenhai; McAvoy, Richard; Li, Wei; Li, Yi
Abstracts: Grafting is a highly useful technique, and its success largely depends on graft union formation. In this study, we found that root-specific expression of the auxin biosynthetic gene iaaM in tobacco, when used as rootstock, resulted in more rapid callus formation and faster graft healing. However, overexpression of the auxin-inactivating iaaL gene in rootstocks delayed graft healing. We observed increased endogenous auxin levels and auxin-responsive DR5::GUS expression in scions of WT/ iaaM grafts compared with those found in WT/WT grafts, which suggested that auxin is transported upward from rootstock to scion tissues. A transcriptome analysis showed that auxin enhanced graft union formation through increases in the expression of genes involved in graft healing in both rootstock and scion tissues. We also observed that the ethylene biosynthetic gene ACS1 and the ethylene-responsive gene ERF5 were upregulated in both scions and rootstocks of the WT/ iaaM grafts. Furthermore, exogenous applications of the ethylene precursor ACC to the junction of WT/WT grafts promoted graft union formation, whereas application of the ethylene biosynthesis inhibitor AVG delayed graft healing in WT/WT grafts, and the observed delay was less pronounced in the WT/ iaaM grafts. These results demonstrated that elevated auxin levels in the iaaM rootstock in combination with the increased auxin levels in scions caused by upward transport/diffusion enhanced graft union formation and that ethylene was partially responsible for the effects of auxin on grafting. Our findings showed that grafting success can be enhanced by increasing the auxin levels in rootstocks using transgenic or gene-editing techniques.